2021
DOI: 10.21203/rs.3.rs-507866/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Venoarterial Extracorporeal Membrane Oxygenation as Mechanical Circulatory Support in Adult Septic Shock: A Systematic Review and Meta-Analysis with Individual Participant Data Meta-Regression Analysis.

Abstract: Background: While recommended by international societal guidelines in the paediatric population, the use of venoarterial extracorporeal membrane oxygenation (VA-ECMO) as mechanical circulatory support for refractory septic shock in adults is controversial. We aimed to characterise the outcomes of adults with septic shock requiring VA-ECMO, and identify factors associated with survival.Methods: We searched Pubmed, Embase, Scopus and Cochrane databases from inception until 1st April 2021, and included all releva… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Survival rates among patients with severely reduced left ventricular ejection fraction (<20%) were 62% in a recent meta-analysis. 3 We described the course of transaminases (Figure 1) that helped to identify acute heart failure at an early stage, and eventually indicated recovery of the patient as a marker of successful right ventricular unloading and adequate systemic perfusion. Slattery and colleagues 4 also reported that abnormal liver function tests were among the first abnormalities in a comparable case.…”
Section: Discussionmentioning
confidence: 99%
“…Survival rates among patients with severely reduced left ventricular ejection fraction (<20%) were 62% in a recent meta-analysis. 3 We described the course of transaminases (Figure 1) that helped to identify acute heart failure at an early stage, and eventually indicated recovery of the patient as a marker of successful right ventricular unloading and adequate systemic perfusion. Slattery and colleagues 4 also reported that abnormal liver function tests were among the first abnormalities in a comparable case.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes vary with age and clinical presentation, with neonates faring better on ECMO, 14 and those with septic cardiomyopathy responding more favourably than those without. 15 VA ECMO with higher flow is associated with improved survival in paediatric sepsis. 16 As indications for ECMO have expanded, there is also a reciprocal decline in absolute and relative contraindications (Table 2).…”
Section: Indications and Contraindicationsmentioning
confidence: 98%
“…As such, there is robust literature specific to its role in cardiac surgery and the cardiothoracic ICU (CTICU) 17,18 . Recent descriptions show a wide array of use beyond the paradigm of postcardiotomy shock in the CTICU as demonstrated by the advent of specialized respiratory ECMO units, mobile ECMO teams, and multidisciplinary shock teams 1–13,19–22 . It is unknown how expanding indications and novel/non‐CTICU locations may affect the delivery of ECMO given this historical context.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…As indications for extracorporeal membrane oxygenation (ECMO) have expanded, its use among different ICU settings has grown. [1][2][3][4][5][6][7][8][9][10][11][12][13] From its origins in cardiopulmonary bypass and the early respiratory support trials of the 1970s to the recent CESAR and EOLIA era, ECMO has typically been dichotomized into either cardiac or respiratory support. [14][15][16] As such, there is robust literature specific to its role in cardiac surgery and the cardiothoracic ICU (CTICU).…”
Section: Introduction/ Backgroundmentioning
confidence: 99%
See 1 more Smart Citation